2017
DOI: 10.1007/s11239-017-1562-5
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism prophylaxis in medically ill patients: a mixed treatment comparison meta-analysis

Abstract: The American College of Chest Physicians guidelines recommend unfractionated heparin (UFH), low molecular weight heparins (LMWHs) or fondaparinux for prevention of venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), in medically-ill patients. Direct oral anticoagulants (DOACs) have been evaluated relative to enoxaparin for VTE prophylaxis though head-to-head comparisons of these agents are lacking. Therefore, we conducted a mixed treatment comparisons meta-analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
8
0
4
Order By: Relevance
“… 6 In comparison, our study showed a very high incidence of VTE (61.1%) in catatonic cases. It is possible that this seemingly high VTE percentage may be related to the following factors specific to this study: the incidence of PE that could not be detected by lower limb ultrasonography was high 44.4% (8/18), contrast-enhanced CT has a higher diagnostic rate of DVT compared to lower limb ultrasonography, 10 and heparin prophylaxis for prevention of VTE 11 was not performed in the current study. Previous studies have reported a DVT incidence of 11.6% in restrained patients, 5 as compared to the low value of 4.1% observed for VTE in this study.…”
Section: Discussionmentioning
confidence: 79%
“… 6 In comparison, our study showed a very high incidence of VTE (61.1%) in catatonic cases. It is possible that this seemingly high VTE percentage may be related to the following factors specific to this study: the incidence of PE that could not be detected by lower limb ultrasonography was high 44.4% (8/18), contrast-enhanced CT has a higher diagnostic rate of DVT compared to lower limb ultrasonography, 10 and heparin prophylaxis for prevention of VTE 11 was not performed in the current study. Previous studies have reported a DVT incidence of 11.6% in restrained patients, 5 as compared to the low value of 4.1% observed for VTE in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Dear Editors, Low-molecular-weight heparins (LMWHs) are used for the prevention of venous thromboembolism (VTE) [1]. Compared to unfractionated heparin (UFH), they offer a number of advantages, including a simplified dosing schedule, improved adherence and decreased risk for heparin-induced thrombocytopenia [2,3]. Severe chronic kidney disease (CKD) represents a high risk for VTE in hospitalised patients (1)(2)(3).…”
mentioning
confidence: 99%
“…Compared to unfractionated heparin (UFH), they offer a number of advantages, including a simplified dosing schedule, improved adherence and decreased risk for heparin-induced thrombocytopenia [2,3]. Severe chronic kidney disease (CKD) represents a high risk for VTE in hospitalised patients (1)(2)(3). Clinicians typically prefer UFH over LMWH for thromboprophylaxis in severe CKD because of concerns with bioaccumulation and possible increased risk for bleeding [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В отдаленном периоде после ТГВ формируется посттромботическая болезнь нижних конечностей или хроническая тромбоэмболическая легочная гипертензия (ХТЭЛГ). В первом случае происходит глубокая дезорганизация работы венозной системы нижних конечностей с высокой вероятностью развития трофических язв и рецидива венозного тромбоза, а при ХТЭЛГ формируется правожелудочковая недостаточность, напрямую связанная с массивностью поражения легочного русла [4]. Тяжелая ХТЭЛГ в течение 5 лет приводит к смерти 10-15% больных, перенесших массивную ТЭЛА.…”
unclassified